2020
DOI: 10.2147/ccid.s265477
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sun Awareness and Sun Protection Practices</p>

Abstract: Background: The incidence of skin cancer has increased over the past few years, owing to excessive exposure to ultraviolet (UV) radiation. Over the past decade, protection against solar radiation has been highly encouraged in numerous public health education campaigns. The adopted sun protection practices include avoiding exposure to the sun, using protective clothing, and applying sunscreen. The aim of this paper was to analyze the awareness and attitudes towards sun protection practices in some regions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…AlGhamdi et al claimed that about half of the respondents showed awareness about the association of sun exposure with skin cancer risk 12 . A similar result has been found by Al Robaee 14,17 . This awareness level is viewed to be low compared to similar researches conducted in the western population 29 .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…AlGhamdi et al claimed that about half of the respondents showed awareness about the association of sun exposure with skin cancer risk 12 . A similar result has been found by Al Robaee 14,17 . This awareness level is viewed to be low compared to similar researches conducted in the western population 29 .…”
Section: Discussionmentioning
confidence: 73%
“…The author also found that only 30% of the participants are conscious of the UV index, and only 20% identified the accurate meaning of the UV index 17 . Based on the several studies about public awareness toward sun protection, 12,14,17,29,67 women are more likely to be familiar with the harmful effects of sun on the skin and take protective measures more appropriately, including sunscreen application. On the other hand, men and residents with low educational levels had more inadequate knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Saudi Arabia, due to its climate, skin cancer ranks 9 th cancer among both sexes (Alamri et al, 2016). However, it can be prevented by proper skin protection afforded by protective wear, and the proper use of sunscreens that have an essential role in protection against UV rays (Sultana, 2020). Using sunscreens protects skin from harmful sun rays and subsequent burns.…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%